QiShenYiQi Pills Attenuates Ischemia/Reperfusion-Induced Cardiac Microvascular Hyperpermeability Implicating Src/Caveolin-1 and RhoA/ROCK/MLC Signaling - Pan, Chun-Shui; Yan, Li; Lin, Se-Qi; He, Ke; Cui, Yuan-Chen; Liu, Yu-Ying; Hu, Bai-He; Chang, Xin; Zhao, Xin-Rong; Fan, Jing-Yu; Han, Jing-Yan (Frontiers in Physiology, 2021)
Aims: Coronary microvascular hyperpermeability is an important contributor to ischemia/reperfusion (I/R) injury. However, the effective strategy for this insult remains limited. The present study aimed to explore the protective effect of the compound Chinese medicine QiShenYiQi Pills (QSYQ) against coronary microvascular hyperpermeability after cardiac I/R with focusing on the underlying mechanism. Methods and Results: Male Sprague-Dawley rats under anesthesia were subjected to occlusion of left coronary anterior descending artery followed by reperfusion. QSYQ was administrated 90 min before ischemia initiation. Human cardiac microvascular endothelial cells (HCMECs) underwent hypoxia/reoxygenation (H/R) challenge with QSYQ administrated 1 hour prior to hypoxia. QSYQ exhibited effects on attenuating microvascular damage and albumin leakage after I/R injury, showing a role in maintaining endothelial junctions, caveolae and collagen in basement membrane of microvessles. Study using HCMECs disclosed that QSYQ protected endothelial barrier from impairment by H/R, attenuating the decline of respiratory chain complex I and ATP synthase, activation of Src/caveolin-1 and increase of RhoA/ROCK/p-MLC, MMP-9 and CTSS. PP2, a Src inhibitor, partially imitated the effect of QSYQ. Conclusions: QSYQ was able to prevent I/R-induced cardiac microvascular hyperpermeability via a mechanism involving Src/caveolin-1 and RhoA/ROCK/MLC signaling.